Divide both sides by -3:
b = 24/(-3) = -8
Chat with our AI personalities
2ab - 3b2 - 3b + 2a does not have a solution, as it is not an equation.
-3b=96+b -4b=96 b=-24
-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1
If 3b = 39 thenb = 39/3b = 13.
3b2 + b - 10 = 0 This quadratic equation can be factored. (3b -5)(b +2) = 0 The equation can be solved when either (3b - 5) = 0, or (b + 2) = 0. If 3b - 5 = 0 then 3b = 5 : b = 5/3 If b + 2 = 0 then b = -2 The roots or solutions to this equation are b = 5/3 and b = -2